Literature Review: Faktor Risiko yang Berhubungan dengan Kejadian Miopia - Muhammad Nadhif Rafii; Rani Himayani; Rekha Nova Iyos; Winda Trijayanthi Utama (Jurnal Studi Multidisiplin Ilmu, 2024)
Purpose: This study aims to review various risk factors associated with the occurrence of myopia based on existing literature. The factors contributing to the development of myopia include genetic, environmental, and individual habits. Limitations: Although this article provides a broad overview of the risk factors associated with the occurrence of myopia, there are several limitations that need to be considered. The studies reviewed in this review come from various geographical contexts and populations, which may limit the generalization of findings to specific groups or locations. Contribution: This article makes a significant contribution to the understanding of risk factors affecting the occurrence of myopia. By analyzing various existing studies, this article presents a comprehensive picture of the relationship between genetic, environmental, and lifestyle factors and the occurrence of myopia. Keywords: Myopia, Myopia Risk Factors, Refractive Errors How to Cite: Rafii ,M.N., Himayani, R., Iyos, R.K., Utama, W.T. (2024). Literature Review: Faktor Risiko yang Berhubungan dengan Kejadian Miopia.Jurnal Studi Multidisiplin Ilmu, 2(2), 65-69.